Penerapan Konseling Trait And Factor Untuk Meningkatkan Pemahaman Karir Pada Warga Binaan Lapas Perempuan Kelas II A Palembang - Ayu Wulandari Ayu; Suryati; Bela Janare Putra (Social Science and Contemporary Issues Journal, 2024)
This research is entitled "Application of Trait and Factor Counseling to Improve Career Understanding in Residents of the Class II A Palembang Women's Prison". The background of this research is that inmates lack a clear understanding of careers, so they experience a sense of lack of self-confidence and confusion in finding work when they are released from prison. Therefore, individual counseling using the Trait And Factor technique is needed. The aim of this research is to find out how to apply individual counseling using the Trait And Factor technique in increasing career understanding among inmates. By using a qualitative approach with case study research methods. The subject in this research is client "I". Techniques for collecting data are interviews, observation and documentation. The results of this research show that after applying individual counseling using the Trait and Factor technique, client "I" experienced very good changes, was more confident, no longer confused, and was able to understand and plan his future career. The implementation of Trait and Factor counseling was carried out in 4 meetings with a 45 minute meeting time. The implementation of individual counseling goes through three stages, namely the initial stage, the core stage, and the final stage.